The Efficacy of Therapeutic Respiratory Muscle Training Interventions in People with Bronchiectasis: A Systematic Review and Meta-Analysis.. - Martín-Valero, Rocío; Jiménez-Cebrián, Ana María; Moral-Muñoz, José Antonio; De La Casa-Almeida, María; Rodríguez-Huguet, Manuel; Casuso Holgado, María Jesús (MPDI, 2020)
Respiratory muscle dysfunction is an important health problem with high morbidity and mortality and associated costs in patients with bronchiectasis (BC). The aim of this study was to analyse the effects of therapeutic respiratory muscle training (RMT) interventions on improving sputum clearance, ventilator function, muscle strength and functional capacity in BC. Methods: Systematic review and meta-analysis were conducted following PRISMA guidelines. Two independent investigators searched using several electronic databases. The methodological quality of nine studies was assessed using the PEDro scale. Study selection/eligibility criteria: The following were included: randomised controlled trials, randomised crossover trials and pilot studies of patients with BC that used the intervention as RMT (inspiratory/expiratory) and evaluations of respiratory muscle strength (maximal expiratory pressure/maximal inspiratory pressure). This systematic review was registered in PROSPERO (CRD42017075101). Nine studies were included, five of which obtained an A recommendation grade, three with B, and one with C. Study quality was poor to good (mean PEDro Score of 6.375 out of 10). Studies had small sample sizes (8–98). Results show improvements on PImax in favour of therapeutic respiratory muscle training intervention (MD = 6.08; 95% CI = 1.38, 10.77; p < 0.01; I2 = 92%). However, high heterogeneity was identified on meta-analysis.
Keywords: Pulmones - Enfermedades; Pacientes - Rehabilitación; Fisioterapia; Músculos respiratorios; Bronchiectasis; Respiratory muscle training; Respiratory muscle strength; Maximum inspiratory pressure; Maximum expiratory pressure; Meta-analysis